ANALISIS DAYA SAING HARGA PARIWISATA INDONESIA: PENDEKATAN ELASTISITAS PERMINTAAN - Utami, Rayinda Citra; Hartono, Djoni (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2017)
Tourism in Indonesia is highly potential, yet it has not given its optimum achievement. The World Economic Forum (WEF) in 2013 ranked Indonesia the 6th and 38th of 140 countries for natural and cultural resources respectively. The rank was far above Thailand and Malaysia. The price competitiveness index of Indonesian tourism ranked 9 of 140 countriesin the same year, yet it doesn’t guarantee the revenue of the tourist destination. If the demand for a destination is inelastic to price, then the price reduction strategy is not able to increase foreign exchange earnings of the destination. Hence, the elasticity of demand precise approach is used to measure the competitiveness of tourism in terms of price. This study used Almost Ideal Demand System models to examine Indonesia’s competitiveness as a tourism destination in comparison with its competitors. Price elasticity suggested that Indonesia is more competitive than Thailand according to the Australian and American tourists. The study also found that Indonesia is more competitive than Malaysia according to the American tourists. The results also indicated that price is the main determinant which influence the spending allocation of tourist in all three countries. By knowing the position of Indonesian tourism competitiveness against competitor countries, the campaign strategies can be created from each country rating in accordance with market demand characteristics. Policy recommendations below are suggested to increase earnings from tourism sector in Indonesia, among others: the need for an appropriate pricing strategy and maintain the stability of domestic inflation, the need to monitor price trends from the competitor countries, and the need for tourism industry cooperation.